The Influence Of Leadership, Organizational Culture, Work Discipline, And Compensation On The Performance Of Employees Of The Park And Hygiene Unit (Tamsih) Of Panca Budi Medan - Nadiya Putri Indah; M. Chaerul Rizky; Yohny Anwar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study was conducted to determine the effect of leadership, organizational culture, work discipline, and compensation on employee performance at the Panca Budi Medan Parks and Cleanliness Unit. The population of this study were all employees of the Panca Budi Medan Parks and Cleanliness Unit, totaling 45 employees, while the sampling technique in this study was probability sampling, namely by using census sampling or saturated sampling because the entire population was sampled if the population was below 100. The results of this study indicate that leadership has a negative and partially insignificant effect on employee performance with a tcount value < ttable (-0,635 < 2,021), organizational culture has a positive and partially insignificant effect on employee performance with a tcount value < ttable (1,211> 2,021), work discipline has a positive and partially significant effect on employee performance with a tcount value > ttable (4,169 > 2,021), and compensation has a positive and partially significant effect on employee performance with a tcount value > ttable (2,363 > 2,021). Simultaneously leadership, organizational culture, work discipline and compensation have a positive and significant effect on employee performance at the Panca Budi Medan Parks and Cleanliness Unit with a value of Fhitung> Ftabel (12,541> 2,61). The results of this study indicate that partially and simultaneously H1 is accepted H0 is rejected. While the resulting coefficient of determination is 51,2% and the remaining 48,8% is explained by other independent variables not examined in this study.